ISLAM, TRADISI DAN INDUSTRIALISASI - Mohammad Masyhur Abadi (Karsa: Journal of Social and Islamic Culture)
AbstracThis article describes the reality that the life integrity of world and after world is the genuine character of Islam. The entity of market and mosque is not opposite due to the fact that they are the power of history converters. Thee task of Islamic generation is to change the wild and the dark side of market into a movement that enable to dynamize the circle of life by taking involve into market dynamic, not by avoiding it. Yet, God is appeared showing the power not only in a mosque but also in a market  Kata-kata kuncimarket, liberalism, fossil technology, mosque